Profissional visual Studio 2013 - Johnson, Bruce (Indiana, Us wiley and sons, 2014)
"This comprehensive guide provides programmers wording on projects for the windows platform a complete overview of Visual Studio 2013, including an in-depth exploration of the new features and changes that have come with the latest iteration. Author and Microsoft MVP Bruce Johnson provides a complete view of the new and updated tools featured in Visual studio 2013 that make programming easier and more efficient. Topics include new shortcuts, UI testing capabilities, and customization options, along with changes to target SharePoint 2013, advanced debugging capabilities, the Data Compare function, and a host of others"
Content : integrated development environment -- Getting started -- Digging deeper -- Rich client application -- Web applications -- Data -- Application services -- Configuration and resources -- Debugging -- Build and deployment -- customizing and extending bisual studio -- Visual studio ultimate
"Also avaliable as an e-book"
"Programmer to programmer"
12
NEW_ZAG_GN
Keywords: Visual Studio 2013; Web sites -- Design